Breaking the Waves: Earthquake and Tsunami Research in the Iberian Peninsula from a Historiographical Perspective. - Álvarez-Martí-Aguilar, Manuel; Machuca Prieto, Francisco (Springer, 2022)
This chapter performs a historiographical overview for the purpose of describing the evolution of recent earthquake and tsunami research in the Iberian Peninsula, characterised by the convergence of information deriving from different scientific disciplines, such as historical seismology, geology and archaeology. From the early 1990s down to the present day, several stages of research are identified, while placing the spotlight on the boom years in geological research on paleotsunamis in Portugal and Spain, in the wake of the catastrophic tsunamis in the Indian Ocean in 2004 and in Japan in 2011, as well as addressing future perspectives for interdisciplinary collaboration. The final section describes the aim of this book, plus the organisation and content of its chapters, as well as reflects on the future challenges facing research in this field.
Política de acceso abierto consultada en http://biblioteca.cchs.csic.es/registro_buscareditoriales.php?id=828
Keywords: Maremotos; Catástrofes naturales; Sismología; Arqueometría; Península Ibérica - Historia antigua; Terremotos; Tsunamis; Sismología histórica; Península ibérica; Historia antigua; Arqueología